Navigating climate resilience in fragile settings: a retrospective analysis of the 2023 flood impacts, early warning, and response in Ethiopia’s Somali Region - Mabumbo, Decide; Nohayi, Ngowenani; Sanchez Ramirez, Juan Carlos; Dessalegn, Mengistu; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
The Fall 2023 floods in the Somali Region of Ethiopia caused widespread devastation, disproportionately affecting vulnerable populations, including refugees, internally displaced persons (IDPs), and host communities. This case study, conducted by the International Water Management Institute (IWMI) as part of the CGIAR Fragility, Conflict, and Migration (FCM) initiative, provides a detailed examination of the systemic factors that exacerbated the disaster's impacts. It evaluates the strengths and weaknesses of early warning systems and offers actionable recommendations to enhance disaster risk management (DRM) in the region. The analysis is based on rigorous desk research and in-depth interviews with key stakeholders, including government officials, humanitarian organizations, non-governmental organizations (NGOs), and development actors, both at the national and subnational levels.